2010
DOI: 10.3390/ph3092821
|View full text |Cite
|
Sign up to set email alerts
|

Role of the G Protein-Coupled Receptor, mGlu1, in Melanoma Development

Abstract: Melanoma remains one of the cancers for which a decline in morbidity has not been achieved with current scientific and medical advances. Mono-therapies targeting melanoma have been largely ineffective, increasing the need for identification of new drugable targets. Multiple tumor suppressors and oncogenes that impart genetic predisposition to melanoma have been identified and are being studied in an attempt to provide insight on the development of anti-melanoma therapies. Metabotropic Glutamate Receptor I (GRM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…mGluR1 has been implicated as an oncogene in melanomagenesis. Wangari-Talbot et al developed a transgenic mouse expressing ectopic GRM1 in melanocytes which was sufficient to induce melanoma (18). Combining the kinase inhibitor sorafenib or the mutant BRaf inhibitor vemurafenib with riluzole had improved antitumor activity in GRM1-expressing melanoma cells harboring either wild-type or mutant B-RAF (19).…”
Section: Introductionmentioning
confidence: 99%
“…mGluR1 has been implicated as an oncogene in melanomagenesis. Wangari-Talbot et al developed a transgenic mouse expressing ectopic GRM1 in melanocytes which was sufficient to induce melanoma (18). Combining the kinase inhibitor sorafenib or the mutant BRaf inhibitor vemurafenib with riluzole had improved antitumor activity in GRM1-expressing melanoma cells harboring either wild-type or mutant B-RAF (19).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies revealed an aberrant expression of mGluR1 in a subset of human melanoma cell lines, suggesting its contribution to melanoma development. Murine studies have shown that activation of mGluR1 induces in vitro melanocytic transformation and in vivo spontaneous melanoma development [ 108 ]. Thus, genetic modulation in the expression of mGluR1 by siRNA or alterations in the transmission of signals mediated by mGluR1 can cause cell proliferation and neoplastic progression [ 109 ].…”
Section: Neurotransmitters and Melanomamentioning
confidence: 99%